2017
DOI: 10.1371/journal.pone.0171648
|View full text |Cite
|
Sign up to set email alerts
|

Engineering characterisation of epoxidized natural rubber-modified hot-mix asphalt

Abstract: Road distress results in high maintenance costs. However, increased understandings of asphalt behaviour and properties coupled with technological developments have allowed paving technologists to examine the benefits of introducing additives and modifiers. As a result, polymers have become extremely popular as modifiers to improve the performance of the asphalt mix. This study investigates the performance characteristics of epoxidized natural rubber (ENR)-modified hot-mix asphalt. Tests were conducted using EN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Previous research has suggested that mixing elastomeric additives with asphalt binder requires a speed between 3000 and 6000 r/min, 10,2327 a time of 30–60 min, 10,23,24,26–28 and a temperature of 140–160°C. 23,24,2629…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that mixing elastomeric additives with asphalt binder requires a speed between 3000 and 6000 r/min, 10,2327 a time of 30–60 min, 10,23,24,26–28 and a temperature of 140–160°C. 23,24,2629…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has suggested that mixing elastomeric additives with asphalt binder requires a speed between 3000 and 6000 r/min, 10,[23][24][25][26][27] a time of 30-60 min, 10,23,24,[26][27][28] and a temperature of 140-160°C. 23,24,[26][27][28][29] In this study, similar to the literature, the process of blending chloroprene rubber (CR) and the base asphalt binder involved using a high shear mixer. Initially, the base asphalt binder was placed in a temperature-controlled container under the mixer and preconditioned for 10 min at 160°C and 4000 r/min to ensure uniformity.…”
Section: Preparation Of Cr-modified Asphalt Bindersmentioning
confidence: 99%
“…Figure 1 shows the gradation of the mixture adopted in this study. The design data for the asphalt mix was taken from an earlier publication by Al-Mansob et al [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…ENR is said to increase the viscosity and rigidity of binders while lowering their temperature susceptibility. Furthermore, the optimal level of the modification in the binder was reported to be 6% ENR [ 12 , 34 , 37 , 38 ]. Therefore, the ENR was employed in this research to eliminate some of the aforementioned NR disadvantages at different environmental conditions, including short- and long-term aging.…”
Section: Introductionmentioning
confidence: 99%
“…Natural rubber was observed to have superior reactivity, which improve the properties of bitumen, such as adhesion, in comparison to other types of rubber used in bitumen modification. NR was also observed to have a strong cohesion with aggregates; this increases the stiffness of bitumen at high temperatures, thereby improving the performance of asphalt mixtures [20]. This review will discuss the sources, types, manufacturing processes, and significance of the use of NR in bitumen modification.…”
mentioning
confidence: 99%